Ethics of Teacher and Student Educative Interaction in The Book Tazkiratu Al-Sami'i Wa Al-Mutakallimi Fi Adabi Al-Alimi Wa Al-Muta'allimi By Imam Ibnu Jama'ah - Arifin, Nur; Ichsan, Ahmad Shofiyuddin (The Magister of Islamic Education IAIN Pontianak, 2024)
This study aims to reveal the ethics of educational interactions between teachers and students in the bookazkiratu al-Sami'i Wa al-Mutakallimi Fi Adabi al-Alimi Wa al-Muta'allimi worksImam Ibn Jama'ah and the relevance of the contents of the book to the dynamics of teacher and student interaction in today's education. This research method is a qualitative research with a type of literature review research and a pragmatic approach. The data analysis uses content analysis. The results of the study show that 1)The ethics that must be adhered to by teachers towards students in educational interactions in the book include: being sincere in educating and teaching, reflecting a close relationship, not being stingy in providing knowledge, not hitting, being sensitive to the environment, and being fair. 2) The ethics that must be adhered to by students towards teachers in the book include: being politeḍu', not arrogant about the knowledge they have, adorn themselves with good morals, be serious in learning, be patient and steadfast in seeking knowledge. The relevance of today's dynamics is that teachers are continuously required to develop creativity in the learning process, so that the interaction between teachers and students always creates a harmonious, humanistic atmosphere, and is full of religious and eastern moral ethics.